KEJADIAN OBESITAS PADA ANAK USIA 6-12 TAHUN - Klise, Maria; da Silva, Maria; Sumilat, Vervando (Lasalle Health Journal, 2022)
Background: Obesity and overweight are two different things, but both of them show an excessive accumulation of fat in the body which is marked by an increase in the value of Body Mass Index (BMI). The cause of obesity in children is not known for certain, but there are several factors influence the occurrence of obesity in children, namely genetic/hereditary factors, eating patterns, activity patterns, gender, and parental education. Objective: To determine whether there is a relationship between genetics/heredity, eating patterns, activity patterns, gender, and parental education with the incidence of obesity in children aged 6-12 years. Methods: This research is a quantitative study using a case-control research design. The case group is obese children and the control group is not obese. This research was conducted at GMIM 54 Lapangan Elementary School. The instrument in this study used a questionnaire sheet and obesity was measured by BMI using a meter to measure height and a scale for weight. The sampling technique was purposive sampling with a sample size of 68 parents with children aged 6-12 years (38 people are the case group and 30 people are the control group). Results: The results showed that eating patterns (p-value 0.000), activity patterns (p-value 0.000), genetics (p-value 0.012), gender (p-value 0.003), and parental education (p-value 0.017) were significantly related to the incidence of obesity. Conclusion: Diet, activity patterns, genetics, parental education, and gender are significantly associated with the incidence of obesity in GMIM 54 Lapangan Elementary School.